EEA Treaty : main agreement and selected protocols. (1992)
Areas covered includes: free movement of goods; free movement of persons, services and capital; competition and other commom rules; horizontal provisions relevant to the four freedoms; cooperation outside the four freedoms; institutional provisions; financial mechanism.
DC